2008
DOI: 10.1186/1745-0179-4-22
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder in late life: clinical characteristics in a sample of older adults admitted for manic episode

Abstract: BackgroundAlthough manic episodes in older adults are not rare, little published data exist on late-life manic episodes. Resistance to treatment and concomitant neurological lesions are frequent correlates of elderly mania. The aim of this study was to investigate the prevalence of hospitalizations due to mania in patients older than 64 years through a period of 5 years in an Italian public psychiatric ward. Moreover, we aimed at describing clinical presentation of elderly manic episodes.MethodsA retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
0
8
0
2
Order By: Relevance
“…Six studies reported the relative proportion of older adults with mania in inpatient psychiatric settings . All studies were retrospective chart reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported the relative proportion of older adults with mania in inpatient psychiatric settings . All studies were retrospective chart reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the paucity of research in geriatric BD, many methodological problems lessen the applicability of the results to older bipolar outpatients under treatment. Most studies regarding this topic were conducted exclusively on patients with a bipolar I subtype disorder after hospitalization in psychiatry wards because of a manic episode (Kennedy et al, 2005;Sajatovic et al, 2005b;Benedetti et al, 2008;Oostervink et al, 2009;Oostervink et al, 2015). Usually a cross-sectional or retrospective design (Sajatovic et al, 2005a;Benedetti et al, 2008) were applied.…”
Section: Introductionmentioning
confidence: 99%
“…While bipolar disorder in geriatric patients remains an area of active interest among investigators, 15 there are relatively few case reports that discuss the approach to symptoms of mania in an elderly patient with no known bipolar history. Arciniegas describes a case of a 60-year-old male with new onset of impulsivity, reduced need for sleep, and labile affect who was given an initial diagnosis of late-onset bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%